2003
DOI: 10.1002/jsfa.1508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moist heat treatment on ruminal nutrient degradability of sunflower seed

Abstract: A study was conducted to determine the effects of moist heat treatment (autoclaving at 127 • C with a steam pressure of 117 kPa for 10, 20 and 30 min) of sunflower seed on crude protein (CP) fractions, ruminal dry matter (DM) and CP degradabilities, and ruminal disappearance of amino and fatty acids. Two ruminally fistulated cows were used in a randomised complete block design. Heating of sunflower seed decreased soluble protein and increased neutral detergent-insoluble protein, with little effect on acid dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
34
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 30 publications
29
34
3
Order By: Relevance
“…On the other hand, there are some studies with regard to heat treatment of sunflower seed. Mustafa et al (2003) reported that autoclaving sunflower seed at 1278C and steam pressure at 117 kPa for 10, 20 and 30 min reduced in situ rumen degradability of CP from 0.910 for the untreated sample to 0.740 for the 30 min treatment. In another study, Schroeder et al (1996) processed sunflower meal in a drum roaster applying different temperatures and drying times.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are some studies with regard to heat treatment of sunflower seed. Mustafa et al (2003) reported that autoclaving sunflower seed at 1278C and steam pressure at 117 kPa for 10, 20 and 30 min reduced in situ rumen degradability of CP from 0.910 for the untreated sample to 0.740 for the 30 min treatment. In another study, Schroeder et al (1996) processed sunflower meal in a drum roaster applying different temperatures and drying times.…”
Section: Discussionmentioning
confidence: 99%
“…The high ED of total-N in SS supports previous values from Mustafa et al (2003) or that assumed by Sauvant et al (2002). On the other hand, its cell wall-bound N had a lower ED (0.559 for NDIN and 0.520 for ADIN) due to the large increase (10.7 and 12.9 times for1 NDIN and ADIN, respectively) of the proportion of undegradable contents.…”
Section: Feed Degradationsupporting
confidence: 90%
“…The intermediate kd value of DM-SS between those NDF and ADF could be associated with the toxicity for microorganisms derived from the seed-fat fermentation (Palmquist and Jenkins, 1980), which should limit the degradation progression. For DM, degradation parameters and ED estimates are in acceptable agreement with previous literature data for SS (Sauvant et al, 2002;Mustafa et al, 2003), WG (Bacha et al, 1992;Arroyo et al, 2009) and WS (Chaudhry, 2000;Shawrang et al, 2013). Present ED estimates for NDF in the latter feed also agree with those indicated by these authors (Chaudhry, 2000;Shawrang et al, 2013).…”
Section: Feed Degradationsupporting
confidence: 89%
“…In general, heat treatment increased NDICP (Mustafa et al, 1999(Mustafa et al, , 2000(Mustafa et al, , 2003Kafilzadeh et al, 2013), but its effect on the acid detergent insoluble protein is different. In some articles, as a result of heat treatment, an increase in the amount of acid detergent insoluble protein (McKinnon et al, 1995) or no change (Mustafa et al, 1999;Kafilzadeh et al, 2013) was observed, and even a decrease (Ganesh & Grieve, 1990;Moshtaghi Nia & Ingalls, 1992;Demjanec et al, 1995;Hsu & Satter, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…In general, an optimum heat treatment could minimize soluble CP and maximize NDICP without a substantial increase in ADICP (Moshtaghi Nia & Ingalls, 1992;McKinnon et al, 1995;Mustafa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%